2022
DOI: 10.15452/cejnm.2022.13.0011
|View full text |Cite
|
Sign up to set email alerts
|

The Turkish version of the Oxford Covid-19 Vaccine Hesitancy Scale

Abstract: Aim: Covid-19 vaccine hesitancy can be an obstacle to the global effort to control the current pandemic. The study aimed to test the validity and reliability of the Turkish version of the Oxford Covid-19 Vaccine Hesitancy Scale. Design: A methodological and descriptive study. Methods: The research was conducted as a methodological and descriptive study. The sample size consisted of 476 academics who voluntarily agreed to participate in the research and completed the online questionnaire between February and Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Namely, higher religiosity and right-wing political orientation were connected with higher institutional trust, which itself was connected with lower vaccine hesitancy. Therefore, this indirect path reduced vaccine hesitancy (2022) and Baumgaertner et al (2018), bearing in mind that they also confirmed the mediating role of the institutional trust within the connection between political identification and vaccine hesitancy, but in the opposite direction than ours. Such findings indicate the importance of contextualizing religiosity and political orientation as determinants of vaccine hesitancy, that is, the importance of ad-hoc factors and specific socio-historical and socio-political circumstances.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Namely, higher religiosity and right-wing political orientation were connected with higher institutional trust, which itself was connected with lower vaccine hesitancy. Therefore, this indirect path reduced vaccine hesitancy (2022) and Baumgaertner et al (2018), bearing in mind that they also confirmed the mediating role of the institutional trust within the connection between political identification and vaccine hesitancy, but in the opposite direction than ours. Such findings indicate the importance of contextualizing religiosity and political orientation as determinants of vaccine hesitancy, that is, the importance of ad-hoc factors and specific socio-historical and socio-political circumstances.…”
Section: Discussionsupporting
confidence: 79%
“…leads to the conclusion that people with higher levels of literacy will have higher levels of trust in science, which ultimately leads to positive attitudes toward vaccines. While there are no studies analyzing the mediating role of trust in science in the context of general vaccines, we can note that Capasso et al (2022) have established the mediating role of trust in science in COVID-19 attitudes in a specific population of unvaccinated men and women. The fact that science literacy was a full mediator in the case of vaccines in general, and only a partial mediator in the case of COVID-19 vaccines, can be explained by the special context in which COVID-19 attitudes have been formed.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations